Polusi udara dan kejadian penyakit kardiometabolik di Indonesia: analisis data IFLS tahun 2014 - Fitri Kusuma Dewi; Lutfan Lazuardi (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
Indoor air pollution and cardiometabolic diseases in Indonesia: an Indonesian Family Life Survey (IFLS) analysis PurposeThe purpose of this study was to determine the relationship between indoor air pollution due to the use of firewood with cardiometabolic disease.MethodsThis research was a prospective cohort study conducted by comparing secondary data of the Indonesian Family Life Survey (IFLS) 2 to IFLS 5. Bivariate analysis used logistic regression and simple Cox regression tests. Multivariate analysis used Cox regression tests.ResultsResults showed exposure to air pollution due to the use of firewood accelerated the incidence of diabetes mellitus by 1.32 times, after controlling for the variables of smoking status, education level, body mass index, waist circumference, and domicile areas. The use of firewood was not correlated to the rate of onset of cardiovascular disease such as CHD and stroke.ConclusionThis research recommends LPG as a replacement fuel.